Model Inkuiri Terbimbing Berbantuan Buku Dongeng Movable Berbasis Etnosains untuk Meningkatkan Literasi Sains Siswa - Izzah Muyassaroh; Septian Mukhlis (AR-RIAYAH: Jurnal Pendidikan Dasar)
Science literacy is an essential skill that elementary school pupils need to be mastered. This study aimed to enhance the sixth-grade students' scientific literacy of SDN Cililitan 02 by implementing a guided inquiry model assisted by an ethnoscience-based movable storytale book. The Kemmis & McTaggart model was utilized in this classroom action research and carried out for 2 cycles of planning, implementation, observation, and reflection. The subjects of this research were 32 sixth-grade students of SDN Cililitan 02 in the academic year 2021-2022. Data collection techniques used in this study included observation, interviews, and tests. The results showed that applying the guided inquiry model assisted by an ethnoscience-based movable storytale book improved the sixth-grade students’ scientific literacy of SDN Cililitan 02. The average scientific literacy percentage of the students in the pre-cycle test was 41.25%. The average percentage of students who completed scientific literacy tests was 67.19% in the first cycle and grew to 85.94% in the second. Applying the guided inquiry model assisted by ethnoscience-based movable fairy tale books makes learning more contextual through scientific methods by presenting local cultural content close to students' daily lives.